Post Mortem Examination and Autopsy Current Issues From Death to Laboratory Analysis - Hakan Dogan, Kamil (IntechOpen, 2018)
Forensic medicine explores the legal aspects of medicine, and medicolegal investigation of death is the most significant and crucial function of it. The nature of post mortem examinations are changing and the understanding of causes of death are evolving with the increase of knowledge, availability, and use of various analyses including genetic testing. Postmortem examination practice is turning into a more multidisciplinary approach for investigations, which are becoming more evidence based. Although there are numerous publications about forensic medicine and post mortem examination, this book aims to provide some basic information on post mortem examination and current developments in some important and special areas. It is considered that this book will be useful for forensic pathologists, clinicians, attorneys, law enforcement officers, and medical students.